„A látvány és a szó szintézisét keresem” Harag György-pályakép - Nánay, István (Symbolon, 2021)
„I am Looking for a Synthesis of Spectacles and Words”, György Harag’s Artistic Career György Harag (1925-1985) has been one of the most significant theater directors of twentieth-century Europe. The site of his activity was mainly in Romania, but he often directed in Hungary and Yugoslavia also. At the beginning of his career his stagings were characterized by psychological realism, connected to Stanislavsky’s name. In turn, after 1960 he sought to articulate the era’s problems using a more modern approach. The decisive change happened in 1971, when he staged the drama of István Nagy: Before the flood, in Târgu Mureş. This time, he neglected the representation of the traditional realist-naturalist milieu, and the action took place on an almost empty stage. From then on, Harag’s performances were marked by their relationship with the Romanian and European tendencies of reteatralization. In his stagings the spectacle was as important as the dramatic text. As a consequence of this turn, the doublespeak, developed in Romania and Eastern Europe under the pressure of dictatorships, has prevailed in his performances